EFFECTS OF ORGANIC ACIDS ON THE DISSOLUTION OF ORTHOCLASE AT 80OC AND PH 6 - Blake R.E.; Walter L.M. (My University, 1996)
The dissolution of K-rich feldspar (orthoclase), quartz and Al(OH)3 was investigated at 80oC and pH 6 in buffered solutions of organic acids. Previous studies of the effects of organic acids (OA) on feldspar dissolution have typically been conducted in acidic, low-ionic strength solutions often under conditions which preclude isolation of effects of pH from those due to organic acids. Our experiments were conducted at constant pH, temperature, ionic strength, and buffer composition to allow direct comparison of experiments with and without OA. The dissolution experiments were conducted under closed-system conditions to: (1) determine the magnitude of mineral solubility enhancement by OA; (2) examine changes in reaction stoichiometry as equilibrium is approached; and (3) investigate the effects of OA on secondary mineral precipitation.The carboxylic acid species, oxalate and citrate, significantly enhanced the dissolution of orthoclase at pH 6. The concentrations of Si and Al in 10 m M oxalate and citrate solutions were nearly 3 times that in solutions of acetate buffer without oxalate or citrate. Aluminum was below the limit of detection (< 0.007 m M) in the acetate buffer alone. Citrate increased the release of Si and Al from orthoclase more than did oxalate at the same concentration. Equilibrium modeling indicates that solutions with oxalate and citrate attained supersaturation with respect to gibbsite, kaolinite, and smectite, and saturation with respect to quartz. Nevertheless, orthoclase dissolution remained congruent with respect to Si and Al release.Separate experiments using pure quartz and Al(OH)3 suggest that a mechanism other than formation of Si-organic complexes may be involved in the OA-enhanced release of Si from orthoclase. The increase in dissolved silica was modest in 10 m M oxalate and 10 m M citrate solutions reacted with quartz, and did not increase with increasing OA concentration. The solubility of quartz was similar in solutions of oxalate and citrate. In contrast, Al(OH)3 dissolution was 50% greater in citrate than in oxalate, similar to the behavior of orthoclase. Citrate may be more effective in dissolving orthoclase than oxalate due to a stronger interaction between citrate and Al, rather than due to a synergistic effect of Al-citrate and Si-citrate complexes. These results have implications for the mass transport of Si and Al in diagenetic environments.